EMPOWERMENT OF ZAKAT FUNDS THROUGH BUSINESS EMPOWERMENT - Wicaksono, Rofiq Guntur; Munir, Maryam Bte Badrul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Public welfare is the main goal of economic development in every country. One of the Islamic economic instruments that can be used to realise welfare in society is zakat. This study analyses the effect of productive zakat utilization in the form of capital and mentoring on mustahik welfare. This research is a quantitative research with Partial Least Square Structural Equation Modelling (PLS-SEM) analysis technique, with SmartPlS 4 software. The object of research is mustahik beneficiaries of the lapak berkah program. The sample used in this study was the entire existing population, namely 80 mustahik beneficiaries of the blessing stall programme. The results showed that capital has no effect on mustahik welfare. Furthermore, the mentoring provided by zakat institutions has no effect on the welfare of mustahiks. This study measures the welfare of mustahik using the maqashid sharia method.  These results can be used as evaluation material related to the utilization of productive zakat funds for the lapak blessing programme, so that it can maximise the benefits to mustahik.